Variability among isolates of Rhizoctonia solani infecting mungbean - M.N. KHARE, ANAMlKA TIWARI and (Indian Phytopathology, 2002)
A total of 108 isolates of R. solani from diseased Vigna radiata samples collected from various locations in Madhya Pradesh, India, were classified into 9 groups designated as I1-I9 based on morphological characteristics. They showed variation in their rate and type of growth, colony colour and time taken for sclerotial production in vitro. Sclerotia were not formed in I3, I6 and I9. Isolate I1 was binucleate while isolates I2-I9 were multinucleate. No anastomosis was observed among the I2-I9 isolates. All isolates were pathogenic. Isolate I3 was the most virulent and caused seed and collar rot as well as leaf blight in V. radiata cv. Pusa Baisakhi.